Finite Element Analysis of the Effect of Tightening Torque on the Connection Stability of a Two-Piece Zirconia Implant System - Hyunsuk Choi; Min-Ho Hong (Advances in Materials Science and Engineering)
Purpose. Loosening and fracture of abutment screws are one of the most common complications in implant-retained fixed prostheses. Thus, applying the proper tightening torque to the abutment screw is important for preventing the loosening effect of the abutment screw and ensuring the stability of the implant fixture-abutment connection. Therefore, in this study, we aimed to investigate the effect of the tightening torque of the abutment screw on the stability of the fixture-abutment connection in a two-piece zirconia implant system using finite element analysis (FEA). Materials and Methods. The two-piece zirconia implant structures used in this study were designed using the CATIA program. The abutment screws with tightening torques of 25 (TT-25), 35 (TT-35), and 45 (TT-45) N·cm were assumed to fix the abutment and fixture. Vertical (200 N) and oblique (100 N) loads were applied to the finite element model generated for FEA simulation, and the stress levels and distributions were investigated. Results. The TT-45 group exhibited the highest von Mises stress in the abutment and fixture, followed by the TT-35 and TT-25 groups. The von Mises and minimal principal stresses of the abutment screw were also highest in the TT-45 group, followed by the TT-35 and TT-25 groups. In all three groups, the area with the highest stress concentration was located at the point of contact with the bottom of the screw head. Furthermore, the TT-25 group showed the highest safety factor value. The TT-35 group showed a safety factor value similar to the safe minimum standard, while the TT-45 group showed a lower safety factor value. Conclusion. When a torque of 35 N cm was applied to the two-piece zirconia implant system, it showed a maximum stress value close to 660 MPa (75% of the yield strength of the Ti-6Al-4V alloy), which is the optimal preload recommended for abutment screws.